Caracterização química e avaliação das atividades antimicrobiana, antinociceptiva e anti-inflamatória do própolis da Melipona quadrifasciata quadrifasciata - Torres, Aledson Rosa (2018)
The demand for natural products with biological application has become of great interest of the scientific community and is not different from the products produced by the bees: honey, propolis, wax and pollen. Several studies have shown the chemical composition and pharmacological properties of africanized bee propolis (Apis mellifera). However, there is a varity of more than 300 species of native bees in the Brazilian fauna, known as stingless bees (meliponineos), which few studies have been carried out, so little is known about the chemical composition and bioactivity of their products. This work aimed to investigate the chemical composition and determine the potential antimicrobial, antioxidant, antinociceptive and anti-inflammatory potential of the hydroalcoholic extract (EHP) of the propolis of Melipona quadrifasciata quadrifasciata. The chemical composition of the EHP was determined by colorimetric and chromatography (HPLC-DAD and UPLC-Q/TOF- MS/MS) analysis. Moreover, the UHPLC-MS analyses of M. quadrifasciata quadrifascita indicated as major constituent’s phenolic compounds, flavonoids and terpenes. The EHP presented antioxidant extracts presented antioxidant activity in the DPPH assay IC50= 241.8 μg/mL. The bactericidal activity was higher against gram-positive bacteria (Staphylococcus aureus, Staphylococcus aureus, meticilina resistente e Enterococcus faecalis)) than for gramnegative bacteria (Escherichia coli e Klebsiella pneumoniae). The EHP from presented MIC values lower to gram-positive bacterials than gram-negative bacterials. The EHP caused lysis of the bacterial wall and release of intracellular components in S. aureus and E. coli, suggesting that this might be one mechanism by which exerts its antibacterial effect EHP. Moreover, the hemolytic activity of S. aureus was significantly lower when incubated in the presence of sub-inhibitory concentrations of EHP. Mice treated by intragastric route with EHP (300 and 1000 mg/kg) showed a significant reduction in nociceptive behavior induced by intraplantar formalin injection, in both phases of the test. While EHP (300 mg / kg) was able to reduce nociception induced by bradykinin, prostaglandin E2, histamine, forskolin, phorbol 12-myristate 13-acetate, capsaicin, cinnamaldehyde and acidified saline. Demonstrating that EHP to modulate the activation of nociceptors by interaction direct with the TRPV1, TRPA1 and ASIC channels and by inhibiting the PKA / PKC signaling pathways. In addition, EHP treatment (300 mg/kg/i.g.) inhibited ear edema induced topically by xylene and inflammatory activity in the carrageenan-induced peritonitis test. Where the anti-inflammatory potential of EHP was established by decreased cell migration, percentage of neutrophils and protein content at the inflammatory site, as well as the decrease of the pro-inflammatory cytokines IL-17 and IL-6 and increase of the anti-inflammatory cytokine IL-10. Thus, this dataset supports, at least in part, the traditional use of the propolis ethanolic extract of Melipona quadrifasciata quadrifasciata.